Children and Stunting Phenomenon in Indonesia: Legal Perspective - Rizka Rizka; Heru Santoso Wahito Nugroho; Arief Budiono; Wafda Vivid Izziyana; Ayesha Hendriana Ngestiningrum (Institute of Medico-legal Publications Pvt Ltd, 2021)
Indonesia is a country with abundant natural resources, yet the case of malnutrition has gone on since a longtime ago. The non-serious handling of malnutrition causes various health conditions such as stunting. Thiswill influence economic capacities and productivity; thus, it becomes a serious threat. This research uses aquantitative method, by using primary and secondary legal sources.Stunting may have implications on children’s health both in the short and in the long run. It may influence thecountry’s economy. The roles of the government, parents, family, and the society is not enough in protectingchildren from stunting. The government has not maximally implied various programs in preventing andhandling stunting, thus the rate of stunting is not yet according to the standard given by WHO. This describessome aspects and the citizens’ rights which are not yet fulfilled, including the rights to live, the right forhealth, the right for children to grow, and other rights.